2020
DOI: 10.1186/s13195-020-00660-z
|View full text |Cite
|
Sign up to set email alerts
|

Visual short-term memory relates to tau and amyloid burdens in preclinical autosomal dominant Alzheimer’s disease

Abstract: Background: Over the past decade, visual short-term memory (VSTM) binding tests have been shown to be one of the most sensitive behavioral indicators of Alzheimer's disease (AD), especially when they require the binding of multiple features (e.g., color and shape). Recently, it has become possible to directly measure amyloid and tau levels in vivo via positron emission tomography (PET). To this point, these behavioral and neurochemical markers have not been compared in humans with AD or at risk for it. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 41 publications
2
44
0
1
Order By: Relevance
“…Recent studies have shown that the temporal lobe is one of the critical areas of pathological changes in multiple types of dementia (Mak et al, 2020;Sanchez et al, 2021). In preclinical AD, tau protein deposition and Aβ burden in the inferior temporal gyrus is related to cognitive performance, mainly memory function (Schultz et al, 2018;Norton et al, 2020;Scott et al, 2020;Vila-Castelar et al, 2020). Tau accumulation in this area may be associated with hippocampal hyperactivity, which is not associated with Aβ (Huijbers et al, 2019).…”
Section: Similar Pattern Between the Obj-scd And Amci Groupsmentioning
confidence: 99%
“…Recent studies have shown that the temporal lobe is one of the critical areas of pathological changes in multiple types of dementia (Mak et al, 2020;Sanchez et al, 2021). In preclinical AD, tau protein deposition and Aβ burden in the inferior temporal gyrus is related to cognitive performance, mainly memory function (Schultz et al, 2018;Norton et al, 2020;Scott et al, 2020;Vila-Castelar et al, 2020). Tau accumulation in this area may be associated with hippocampal hyperactivity, which is not associated with Aβ (Huijbers et al, 2019).…”
Section: Similar Pattern Between the Obj-scd And Amci Groupsmentioning
confidence: 99%
“…swap errors) were not replicated. Notably, a recent FAD study by Norton and colleagues ( Norton et al, 2020 ), found that the condition requiring conjunctive binding of colour and shape was not preferentially linked to tau (measured by positron emission tomography – PET) but rather that the non-binding “shape only” condition showed a stronger relationship. This emphasizes that much remains to be understood about VSTM binding and that group studies comparing conjunctive and relational binding over time, will provide critical data on which processes are affected, at what stage and in which order.…”
Section: Discussionmentioning
confidence: 99%
“…The positive aspect of this is that we have for long needed tests that can detect the very early stages of the disease process, preferably, when people are unaware of or are very little concerned about any cognitive or functional impairment. We have learned that at this stage, the VSTMBT is taxing the early growth of amyloid in at risk individuals even before tau deposits or neurodegeneration become apparent [32,35,38]. Such a test would be an ideal tool for clinical trials aiming at dementia prevention as they could enhance recruitment strategies by selecting who will likely meet inclusion criteria (e.g., Aβ+).…”
Section: Discussionmentioning
confidence: 99%